2006
DOI: 10.1152/ajpregu.00510.2005
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in the renin-angiotensin system in aging spontaneously hypertensive rats

Abstract: Sexual dimorphism in the renin-angiotensin system in aging spontaneously hypertensive rats. Am J Physiol Regul Integr Comp Physiol 291: R383-R390, 2006. First published March 30, 2006 doi:10.1152/ajpregu.00510.2005.-In young adult spontaneously hypertensive rats (SHR), mean arterial pressure (MAP) is higher in males than in females and inhibition of the renin-angiotensin system (RAS) eliminates this sex difference. After cessation of estrous cycling in female SHR, MAP is similar to that in male SHR. The purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
50
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 22 publications
4
50
0
1
Order By: Relevance
“…In fact, reactive oxygen species can modulate calcium handling proteins [48], such as ryanodine receptors, SERCA2a and L-type calcium channels, thereby contributing to slowed calcium transients [49][50][51][52][53]. In the present study, we observed increased levels of oxidative stress and PLBThr" phosphorylation, as reported by others [30,42,46]. Oxidative stress may have contributed to the myocardial contractile dysfunction observed in OVX rats.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In fact, reactive oxygen species can modulate calcium handling proteins [48], such as ryanodine receptors, SERCA2a and L-type calcium channels, thereby contributing to slowed calcium transients [49][50][51][52][53]. In the present study, we observed increased levels of oxidative stress and PLBThr" phosphorylation, as reported by others [30,42,46]. Oxidative stress may have contributed to the myocardial contractile dysfunction observed in OVX rats.…”
Section: Discussionsupporting
confidence: 86%
“…Angiotensin II most likely negatively affects excitation-contraction coupling in the myocardium by increasing Superoxide production in the heart [30]. Estrogen may play a more important role in mediating oxidative stress in males than in females [42]. Prolonged exposure to angiotensin II activates the Ca^V^almodulin-dependent protein kinase (CaMK) II by increasing reactive oxygen species [43] which in turn phosphorylates phospholamban at Thrl 7, increasing calcium reuptake by SERCA2a and leading to cell death [44].…”
Section: Discussionmentioning
confidence: 99%
“…One of the suggested mechanisms underlying this sexual dimorphism is differences in the function of the renin-angiotensin system (RAS). [2][3][4] Angiotensin II (Ang II), the main effector peptide of the RAS, exerts its effects through 2 main receptor subtypes. Stimulation of the angiotensin type 1 receptor (AT 1 R) causes vasoconstriction, sodium reabsorption, and cell proliferation.…”
mentioning
confidence: 99%
“…We have shown previously in other models of hypertension (most are androgen sensitive in the males) that androgens stimulate increases in plasma renin activity and angiotensinogen synthesis. [3][4][5] Thus, one potential mechanism for our findings is activation of the reninangiotensin system in response to the testosterone supplementation in OZRs that mediated the hypertensive response. However, we did not see any increase in blood pressure in the lean Zuckers who also received testosterone supplements.…”
mentioning
confidence: 80%